Studies Of Interpersonal Communication In Adolescents Seen Form The Aspect Of Selfconcept And Self Disclosure - Qudrotin, Lilih; Mulyono, Rachmat (‎‎‎TAZKIYA: Journal of Psychology, 2017)
This study was conducted to determine the dimensions of self concept (self image, selfevaluation, ideal-self, and social self) and self- disclosure (amount, valance, accuracy & honesty, intention, and intimacy) on communication interpersonal adolence. The samples used in this study are 284students in SMPN 1 Rajeg. This study used quantitative method with multiple regression analysis. The results of this study show that self-concept and selfdisclosure have significant influence on self adjustment of new immigrant students in college (R square = 17.6 %, sig = 0,000). The results of minor hypothesis testing show that ideal-self,amount, and valensi significantly influence communication interpersonal of students inSMPN 1 Rajeg. The implications of the findings in terms of providing interventions forincreasing levels of communication interpersonal among students in SMPN 1 Rajeg werediscussed. DOI: 10.15408/tazkiya.v22i1.8161